The CEFR Descriptors for Mediation in an ESP CALL-Based Context: A Case Study - Korai, Maria (Language Center, Cyprus University of Technology, 2019)
Motivated by the unprecedented acknowledgement of mediation as a central concept in the New CEFR Companion (Council of Europe, 2018), the present case study investigated the potential of the CEFR Can-do descriptors for mediation in an ESP CALL-Based context. In the updated New CEFR Companion, mediation is treated as a fundamental mode of communication; not only the significance of the co-construction of meaning but also “the constant movement between the individual and social level in language learning” (CEFR, 2018, p.9) led to the development from scratch of descriptor scales for mediation. However, the CEFR mediation descriptor scales are still underexplored at the moment, especially in ESP CALL-Based language learning contexts. The present research aspired to fill some of this gap in the literature by providing insights regarding the CEFR descriptors for mediation, not just in a general English learning context, but in ESP CALL-Based contexts. The researcher employed a case study research design and mixed research method; she utilised observation, learner self-assessment against Can-do statements for mediation and focus groups interviews to address the research aims: Firstly, the adaptation of the CEFR descriptors for mediation to the existing ESP curriculum revealed high prevalence of mediation in the ESP curriculum despite the designers’ unawareness of the CEFR framework for mediation prior to this study; the systematic presence of mediation in the ESP curriculum provided insights into how mediation was present in the existing ESP curriculum, which was the first research aim. Likewise, the implementation of the existing ESP CALL-Based course activities addressed the second research aim being “how the ESP course activities of this case study support mediation?” The implementation of the ESP course activities revealed their potential to support mediation processes and highlighted the significance of the CALL component of the ESP course activities to trigger, support and promote mediation processes. Finally, the revelation of the participants’ positive perceptions of the descriptors for mediation stressed the importance of incorporating them in the ESP course, an insightful finding regarding the third research aim which was “what are the students’ perceptions of the descriptors for mediation.”
Keywords: Mediation; CEFR; CEFR Can-do descriptors; ESP